Insights Into Mitochondrial Dynamics in Chlamydial Infection - Yang, Yewei; Lei, Wenbo; Zhao, Lanhua; Wen, Yating; Li, Zhongyu (Frontiers in Cellular and Infection Microbiology, 2022)
Mitochondria are intracellular organelles that are instrumental in the creation of energy, metabolism, apoptosis, and intrinsic immunity. Mitochondria exhibit an extraordinarily high degree of flexibility, and are constantly undergoing dynamic fusion and fission changes. Chlamydia is an intracellular bacterium that causes serious health problems in both humans and animals. Due to a deficiency of multiple metabolic enzymes, these pathogenic bacteria are highly dependent on their eukaryotic host cells, resulting in a close link between Chlamydia infection and host cell mitochondria. Indeed, Chlamydia increase mitochondrial fusion by inhibiting the activation of dynein-related protein 1 (DRP1), which can regulate host cell metabolism for extra energy. Additionally, Chlamydia can inhibit mitochondrial fission by blocking DRP1 oligomerization, preventing host cell apoptosis. These mechanisms are critical for maintaining a favorable environment for reproduction and growth of Chlamydia. This review discusses the molecular mechanisms of mitochondrial fusion and fission, as well as the mechanisms by which Chlamydia infection alters the mitochondrial dynamics and the prospects of limiting chlamydial development by altering mitochondrial dynamics.